Pengaruh Perencanaan Strategi Bank Mandiri Terhadap Kinerja Perusahaan(Studi Kasus: Bank mandiri pusat bagian Corporate Banking) - Friska Sari Asta; siti safaria (Sekolah Pascasarjana Perbanas Jakarta, 2018)
A good organization has a clear purpose based on the vision and mission agreed upon by its founder. To realize that goals needed a way to achieve that is a strategy. This study aims to analyze the influence between : the development of strategies for internet banking and e-money products on the performance of the company, the implementation of the strategy of internet banking and e-money products to company performance and strategic strategy planning for internet banking products and e-money on the performance of the company. The method of research conducted in this research is descriptive method with correlational type. The population in this study are employees of Bank Mandiri Corporate Banking which amounted to 235 employees. Samples in this study were 148 employees. Sampling technique used is probability sampling. Probability sampling is a sample technique that provides equal opportunity for each element (member) of the population to be elected as a sample member. This research uses explanatory survey method which is a research method conducted on large and small population. Based on the above calculation, it is known that there is partial or simultaneous the influence between strategy development variable and strategy implementation toward organization performance for internet banking and e-money product. This research is in line with research conducted Nurhapna, Setya Haksam. The results of this study suggests that the existing strategic planning in Muhammadiyah Lamongan Hospital in 2014 is sufficiently categorized. Keywords: Strategic Planning, Corporate Performance.